PENUNDAAN PENJEPITAN TALI PUSAT SEBAGAI STRATEGI YANG EFEKTIF UNTUK MENURUNKAN INSIDEN ANEMIA DEFISIENSI BESI PADA BAYI BARU LAHIR - Kurniawan Artha, Ida Bagus Rendra; Kemara, Ketut Putera; Megadhana, I Wayan (E-Jurnal Medika Udayana; vol 2 no 9 (2013):e-jurnal medika udayana, 2013)
Normal 0 false false false EN-US X-NONE X-NONE Iron Deficiency Anemia in infants is a health problem that is almost in the entire developed world. Iron Deficiency Anemia is an anemia that is common in babies with the highest incidence in 6 to 24 months. The high prevalence of anemia in infants aged 6-9 months is associated with insufficient backup storage of iron in the baby so that it can lead to impaired growth and development within the first 6 months of life. Time of Cord Clamping play an important role in determining the adequacy of iron in the newborn. Cord Clamping is one of active management of the third stage. Delayed Cord Clamping about 2-3 minutes can give the redistribution of blood between the placenta and the baby, giving assistance placental transfusion acquired by infants as much as 35-40 ml/kg and contains 75 mg of iron as sufficient hemoglobin, that fulfill the needs iron newborn babies in first three monthsof his life. /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin-top:0in; mso-para-margin-right:0in; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0in; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: Delayed Cord Clamping, Iron Deficiency Anemia